Biosintesis Nanosilver Menggunakan Ekstrak Kulit Buah Rambutan (Nephelium Lappaceum) L. Di Bawah Iradiasi Sinar Matahari - Ibrahim, Ibrahim; Utami, Umi Baroroh Lili; Mustikasari, Kamilia (LPPM Universitas Sari Mulia, 2025)
Background: The development of more environmentally friendly and sustainable methods for nanosilver synthesis has become crucial. Biosynthesis using plant extracts as reducing agents offers an attractive alternative due to its simple process, low cost, and absence of hazardous waste. Rambutan (Nephelium lappaceum) fruit peel is agricultural waste that potentially contains bioactive compounds, such as phenolic compounds, which can act as reducing agents in the synthesis of metal nanoparticles. The utilization of solar energy as an energy source in the synthesis process is also in line with the principles of green chemistry. Objective: This research aims to synthesize nanosilver using rambutan fruit peel extract and characterize it using UV-Vis spectrophotometry and SEM-EDS. Method: Rambutan fruit peel was macerated with distilled water at 80℃ for 15 minutes. The obtained extract was characterized using UV-Vis spectrophotometry. Nanosilver biosynthesis was carried out by mixing a 50 mM AgNO3 solution with the rambutan peel extract in variations of 1:1, 1:2, 2:0.5, and 2:1. The mixture was homogenized and exposed to sunlight for 15 minutes, then left to stand for 24 hours in a dark room. The formed nanosilver was characterized using UV-Vis spectrophotometry and SEM-EDS. Results: The IR spectra of the rambutan fruit peel extract identified the presence of phenolic OH functional groups at wavenumbers 3300−3400 cm-1 and C=O absorption at 1650 cm-1. The presence of phenolics acted as a reducing agent. The formed nanosilver had a pore size of 78.8-204 nm. The absorption peak of surface plasmon resonance (SPR) was in the range of 360−413 nm. Conclusion: The formed nanosilver has pores of 78.8-204 nm and tends to be spherical in shape, with a Surface Plasmon Resonance (SPR) absorption peak at 360-413 nm.